2017
DOI: 10.1021/acscatal.7b03551
|View full text |Cite
|
Sign up to set email alerts
|

Electro-oxidative C(sp3)–H Amination of Azoles via Intermolecular Oxidative C(sp3)–H/N–H Cross-Coupling

Abstract: A method for electrooxidative C­(sp3)–H amination via intermolecular oxidative C­(sp3)–H/N–H cross-coupling has been developed under metal- and oxidant-free conditions. The C­(sp3)–H bonds adjacent to oxygen, nitrogen, and sulfur atoms could all react smoothly with various amines to give the corresponding products with moderate to good yields (30–93%). In addition, the C­(sp3)–H bonds of benzylic and allylic are also tolerated in this reaction. A preliminary mechanistic study indicates that the C–H cleavage of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
91
1
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 185 publications
(96 citation statements)
references
References 56 publications
0
91
1
4
Order By: Relevance
“…[77] Three types of crystalline starch polymorphs are proposed in plants, A, B, and C. [56] A-and B-type polymorphs are considered to have a double helical structure but differ in their compactness [56] while the C-type polymorph is thought to be a mixture of type-A and type-B polymorphs. [56] Starch crystalline structures were modelled by Imberty and Perez [78,79] based on the X-ray diffraction patterns generated by Wu and Sarko [80,81] (Figure 2). These studies suggested type-A and type-B polymorphs have identical double helical pairing but differ in water content and packing of the helices.…”
Section: Effect Of Starch Granule Size Crystallinity Amylose Contenmentioning
confidence: 99%
See 1 more Smart Citation
“…[77] Three types of crystalline starch polymorphs are proposed in plants, A, B, and C. [56] A-and B-type polymorphs are considered to have a double helical structure but differ in their compactness [56] while the C-type polymorph is thought to be a mixture of type-A and type-B polymorphs. [56] Starch crystalline structures were modelled by Imberty and Perez [78,79] based on the X-ray diffraction patterns generated by Wu and Sarko [80,81] (Figure 2). These studies suggested type-A and type-B polymorphs have identical double helical pairing but differ in water content and packing of the helices.…”
Section: Effect Of Starch Granule Size Crystallinity Amylose Contenmentioning
confidence: 99%
“…These studies suggested type-A and type-B polymorphs have identical double helical pairing but differ in water content and packing of the helices. [78][79][80][81] X-ray diffraction and microscopic analysis of rice starch by Maningat [75] suggested that only type-A polymorphs are present in raw rice. Another semi-crystalline rice starch structure has been proposed, namely V-type ( Figure 2) in which the starch molecule surrounds non-starch compounds such as lipid.…”
Section: Effect Of Starch Granule Size Crystallinity Amylose Contenmentioning
confidence: 99%
“…[4] Direct C(sp 3 )ÀNb ond formation thougho xidative CÀH/NÀHc ross-coupling remains challenging owing to the great difficulties in activating the C(sp 3 )ÀHb ond. [5] Althoughs omep ioneer work has been performed concerning the direct C(sp 3 )ÀHa midation under transition-metal catalysis and metal-free conditions (Scheme 1.2), [6] somel imitations still exist for theset ransformations, such as the use of transition metals or excess externalo xidants, harsh reactionc onditions, poor tolerance towards substituents, and so on. Therefore, it is necessary to develop an ew strategy to synthesize N-Mannich bases through oxidative CÀH/NÀHc ross-coupling.…”
mentioning
confidence: 99%
“…Nature has formed various ingenious and nearly perfect structures, contributing to their extraordinary functionalities. Helical structure is one of the most remarkable examples that presents in many different contexts and scales throughout nature, from the molecular level helical structure of DNA, RNA, proteins, and polysaccharides, [1][2][3][4] to microscopic helical vessels, bacterial flagella, spirulina and viral capsids, [5,6] to macroscopic seed pods, plant tendrils, and vasculatures. [7,8] Inspired by the features of these structural-functional adaptations, increasing efforts have been devoted to the achievements of synthetic materials/devices with helical fiber structures, including swimmer, artificial skin, field-effect transistors, wearable devices and robotics, etc.…”
mentioning
confidence: 99%